Learning Style Analysis of Semester 7 GPA In Medical Study Program Students Class of 2019 at The Faculty of Medical and Health Sciences UKRIDA - Budiman Hartono (Jurnal MedScientiae, 2023)
The learning style used by individuals is a significant factor in the learning process which will have an impact on the achievement of learning outcomes. In a quantitative data-based approach, information about learning styles and academic achievement was collected from a sample group of 2019 class students. The main objective of this study was to evaluate the learning styles adopted by UKRIDA Medical students’ class 2019, and their academic achievement achievements (GPA). Of the 62 students, it was found that the majority of students from the Ukrida Medical Faculty Class of 2019 have a kinesthetics’ learning style. The results of this study are expected to provide insight into the importance of understanding learning styles in improving the academic achievement of UKRIDA Faculty of Medicine students as well as providing input for the development of learning methods that are more in line with their learning characteristics.